2008
DOI: 10.1097/hjh.0b013e3282f240bf
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid stimulates vascular smooth muscle cell proliferation and oxidative stress via the vascular renin–angiotensin system

Abstract: These results demonstrate that uric acid stimulates proliferation, angiotensin II production, and oxidative stress in VSMC through tissue RAS. This suggests that uric acid causes cardiovascular disorders by stimulating the vascular RAS, and this stimulation may be mediated by the MAP kinase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
497
0
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(529 citation statements)
references
References 27 publications
13
497
0
19
Order By: Relevance
“…Previous reports have shown that uric acid induces endothelial dysfunction and smooth muscle cell proliferation by activating the RAS and inflammatory mediators such as tumor necrosis factor-alpha and mitogen-activated protein kinases, which are known to induce cardiac hypertrophy [1,10,11,30]. It has been also reported that uric acid in vitro may increase endothelin-1 gene expression in rat cardiac fibroblasts [12].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports have shown that uric acid induces endothelial dysfunction and smooth muscle cell proliferation by activating the RAS and inflammatory mediators such as tumor necrosis factor-alpha and mitogen-activated protein kinases, which are known to induce cardiac hypertrophy [1,10,11,30]. It has been also reported that uric acid in vitro may increase endothelin-1 gene expression in rat cardiac fibroblasts [12].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, uric acid is thought to induce experimentally cardiomyocyte growth and interstitial fibrosis of the heart, in part via activation of the renineangiotensin system (RAS) [10,11] and in part by inducing endothelin-1 gene expression in cardiac fibroblasts [12].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, reactive oxygen species are generated by xanthine oxidase that may impair nitric oxide production, and consequently induce endothelial dysfunction, and impair mitochondrial ATP production 33. UA may also stimulate production of C‐reactive protein, inhibit endothelial cell proliferation, which can also cause endothelial dysfunction,34 induce smooth muscle cell proliferation, and increase the production of angiotensin II 35. However, UA is excreted by the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…30 There are multiple ways in which UA can most likely cause vascular remodelling. UA can alter the proliferation and migration of vascular smooth muscle cells 31,32 by activating a series of pathways including mitogen-activated protein kinases, 32,33 platelet-derived growth factors, chemokines (monocyte chemoattractant protein-1), and inflammatory enzymes (COX-2). 32,33 Besides its possible direct effect on vascular smooth muscle cells proliferation and migration, UA may also exert other detrimental effects on the vascular system.…”
Section: Discussionmentioning
confidence: 99%